PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Putra, Pendra Eka; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on the background of the phenomenon that occurred in the field is still a lack of development that occurred in the Village District Tanjung Koto Kampar such as the construction of post ronda which until now not ready to build, and semenisasi unfinished roads, public services provided by the village government is still not satisfied According to society and society still not prosperous because society still feel difficult emndapatkan service from government which exist in Desa Tanjung Subdistrict Koto Kampar. The formulation of the problem in this research is how the Village Fund Allocation Management (ADD) in the Village of Tanjung Koto Kampar Hulu Sub-district of Kampar District and the factors that influence the Village Fund Allocation Management (ADD) in the Village of Tanjung Koto Kampar Hulu Subdistrict, Kampar regency. The type used in this research is qualitative with descriptive survey technique. The location of this research was conducted in Desa Tanjung Koto Kampar Hulu sub-district, Kampar regency. The informant is the Head of Tanjung Village, the Secretary of Tanjung Village Head, and the community. The results of the implementation of Village Fund Allocation (ADD) management in the physical development of the Tanjung Village can be seen from the results of the research interviews, that the management carried out is in accordance with the planning discussed, but the problem is the lack of supervision by the village government to the people who commit the fraud so that Hampering the management of Village Fund Allocation (ADD) in the physical development of Desa Tanjung. And the factors affecting the management of Tanjung's village funding allocations are that the lack of finances owned by Tanjung villages is exacerbated by the sluggish assistance from local governments in providing village allocation funds, the lack of village community participation in village development that is part of village financial management makes it even more difficult for successful financial management, Supporting factors and constraints to village financial management are on the internal and external side of the village organization. These factors greatly affect the performance of Tanjung village's financial management while the inhibiting factor of village financial management is the limited availability of funds so that managers the difficulty of determining which programs should be precedence.Keywords: Management, Allocation of Village Funds